Coccostromopsis palmicola on Butia yatay from Argentina - Capdet, Mariana (2010)
Coccostromopsis palmicola on living leaves of Butia yatay (Arecaceae) is reported for the first time from Argentina. This fungus is briefly described and illustrated. Some phytogeographical and phythopathological aspects are discussed.